Exploring the boundaries of rhetoric. Issue 5 (11th August 2014) - Bonet, Eduard
Abstract : Purpose: – The purpose of this paper is to examine how the boundaries of rhetoric have excluded important theoretical and practical subjects and how these subjects are recuperated and extended since the twentieth century. Its purpose is to foster the awareness on emerging new trends of rhetoric. Design/methodology/approach: – The methodology is based on an interpretation of the history of rhetoric and on the construction of a conceptual framework of the rhetoric of judgment, which is introduced in this paper. Findings: – On the subject of the extension of rhetoric from public speeches to any kinds of persuasive situations, the paper emphasizes some stimulating relationships between the theory of communication and rhetoric. On the exclusion and recuperation of the subject of rhetorical arguments, it presents the changing relationships between rhetoric and dialectics and emphasizes the role of rhetoric in scientific research. On the introduction of rhetoric of judgment and meanings it creates a conceptual framework based on a re-examination of the concept of judgment and the phenomenological foundations of the interpretative methods of social sciences by Alfred Schutz, relating them to symbolic interactionism and theories of the self. Originality/value: – The study on the changing boundaries of rhetoric and the introduction of the rhetoric of judgment offers a new view on the present theoretical and practical development of rhetoric, which opens new subjects of research and new fields of applications.